2012
DOI: 10.3389/fpsyg.2012.00014
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Face Distortion Aftereffects for Differences in Expression or Gender

Abstract: The perceived configuration of a face can be strongly biased by prior adaptation to a face with a distorted configuration. These aftereffects have been found to be weaker when the adapt and test faces differ along a number of dimensions. We asked whether the adaptation shows more transfer between faces that share a common identity, by comparing the strength of aftereffects when the adapt and test faces differed either in expression (a configural change in the same face identity) or gender (a configural change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Adaptation studies show that prior exposure to a variety of stimulus features (Anstis, Verstraten, & Mather, 1998;Campbell & Maffei, 1971;Webster et al, 2004) results in a stimulus-specific negative aftereffect, or perceptual repulsion, away from the adapting stimulus (for reviews see Thompson & Burr, 2009;Webster, 2012). Additionally, both emotional expression and facial identity have previously been reported to exhibit negative aftereffects (Carbon & Leder, 2005;Fox & Barton, 2007;Fox, Oruc, & Barton, 2008;Leopold, Rhodes, Muller, & Jeffery, 2005;Rhodes, Jeffery, Clifford, & Leopold, 2007;Tillman & Webster, 2012;Webster & MacLin, 1999;Webster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation studies show that prior exposure to a variety of stimulus features (Anstis, Verstraten, & Mather, 1998;Campbell & Maffei, 1971;Webster et al, 2004) results in a stimulus-specific negative aftereffect, or perceptual repulsion, away from the adapting stimulus (for reviews see Thompson & Burr, 2009;Webster, 2012). Additionally, both emotional expression and facial identity have previously been reported to exhibit negative aftereffects (Carbon & Leder, 2005;Fox & Barton, 2007;Fox, Oruc, & Barton, 2008;Leopold, Rhodes, Muller, & Jeffery, 2005;Rhodes, Jeffery, Clifford, & Leopold, 2007;Tillman & Webster, 2012;Webster & MacLin, 1999;Webster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effects of gender adaptation can be investigated after relatively short and long delays between faces of the same or different age groups, ethnicities, or gaze points. A related investigation focused on transfer effects between different emotional expressions and gender in the context of FDAEs (Tillman and Webster, 2012). This systematic investigation of the interplay of delay and transfer may provide conclusions about the range of adaptation effects and their origin from similar or different methods of neural coding.…”
Section: Future Investigations Of Face Adaptation Effectsmentioning
confidence: 99%
“…Previous studies examining the effect of inversion on FAEs (see above) suggested that these facial properties might also be important for aftereffects of gender and distortion. In case of distortion, a recent study has shown that the FDAE is contingent on emotional expression and gender, which might indicate that the underlying processing sites are sensitive to configural changes that differentiate between faces varying along these dimensions (Tillman and Webster, 2012). However, as the authors note, these results can be explained by the adaptation of processing sites engaged in more generic visual processing, and do not necessarily involve face-specific response changes.…”
Section: Introductionmentioning
confidence: 99%